Energy for Europe : Economic and Political Implications - Carmoy, Guy de. (Washington : American Enterprise Institute for Public Policy Research, 1977)
The purpose of this book is to analyze the energy situation in Western Europe at present and over the next decade.
Includes bibliographical references.
ne 13/04/2018
Loans
Keywords: Energy Policy; Power Resources